Evaluating the reading and listening outcomes of beginning‐level Duolingo courses - Jiang, Xiangying; Rollinson, Joseph; Plonsky, Luke; Gustafson, Erin; Pajak, Bozena (Foreign language annals, 2021)
Duolingo is a commercial language‐teaching platform that offers free courses on the web and on mobile apps. This study reports the ACTFL listening and reading proficiency levels of adult Duolingo learners who had completed beginning‐level courses in Spanish or French. The participants (n = 225) were learners residing in the United States, had little to no prior proficiency in the target language, and used Duolingo as their only learning tool. The Duolingo learners reached Intermediate Low in reading and Novice High in listening. No other skills were assessed. Their reading and listening scores were comparable with those of university students at the end of the fourth semester of study. The findings of the study suggest that Duolingo can be an effective tool for foreign language learning. The Challenge As more and more learners use digital apps to learn languages, it is important for the field of language learning to understand the effectiveness of these apps. This article presents the listening and reading proficiency of Duolingo learners when they reach the end of its beginning‐level Spanish and French courses.